Analisis Kebutuhan Tenaga Kerja Pengemasan Kertas B5 Menggunakan Time Motion Study di PT XCX - Paripurna, Panca; Nugraha, Asep Erik; Kusnadi, Kusnadi; Al Fauzan, Vikri; Syah, Gusti Muhammad Yngwei Rayhan (Fakultas Teknik Universitas Tulang Bawang, 2026)
The paper packaging process plays an important role in ensuring the quality and efficiency of product distribution, but is often not supported by optimal labor allocation. Inefficient labor allocation at PT XCX leads to resource wastage, thereby requiring objective measurements to establish the ideal number of workers. This study aims to analyze work elements, calculate standard time, and determine the number of labor requirements in the B5 size paper packaging process at PT XCX. The research method used is Time Motion Study to measure the duration of each work element and Work Load Analysis based on actual production data of 174,356 reams/month and available working time of 630,000 seconds/month. The results show that the average standard time to complete one packaging cycle is 44.56 seconds, and the ideal number of workers is 12 people. The scientific findings show that the excess of two workers from the actual number (14 people) does not have an impact on increasing productivity, but rather becomes a potential waste. This research contributes to the optimization of human resources based on actual data and suggests the application of similar methods in other production lines with additional ergonomic variables as further development. Keywords: B5 Paper Packaging, Labor Efficiency , Standard Time, Time Motion Study, Work Load Analysis.